Normothermia after decompressive surgery for space-occupying middle cerebral artery infarction: a protocol-based approach - Jan Rahmig; Matthias Kuhn; Hermann Neugebauer; Eric Jüttler; Heinz Reichmann; Hauke Schneider (BMC Neurology, 2017)
Abstract Background Moderate hypothermia after decompressive surgery might not be beneficial for stroke patients. However, normothermia may prove to be an effective method of enhancing neurological outcomes. The study aims were to evaluate the application of a pre-specified normothermia protocol in stroke patients after decompressive surgery and its impact on temperature load, and to describe the functional outcome of patients at 12 months after treatment. Methods We analysed patients with space-occupying middle cerebral artery (MCA) infarction treated with decompressive surgery and a pre-specified temperature management protocol. Patients treated primarily with device-controlled normothermia or hypothermia were excluded. The individual temperature load above 36.5 °C was calculated for the first 96 h after hemicraniectomy as the Area Under the Curve, using °C x hours. The effect of temperature load on functional outcome at 12 months was analysed by logistic regression. Results We included 40 stroke patients treated with decompressive surgery (mean [SD] age: 58.9 [10.1] years; mean [SD] time to surgery: 30.5 [16.7] hours). Fever (temperature > 37.5 °C) developed in 26 patients during the first 96 h after surgery and mean (SD) temperature load above 36.5 °C in this time period was 62,3 (+/− 47,6) °C*hours. At one year after stroke onset, a moderate to moderately severe disability (modified Rankin Scale score of 3 or 4) was observed in 32% of patients, and a severe disability (score of 5) in 37% of patients, respectively. The lethality in the cohort at 12 months was 32%. The temperature load during the first 96 h was not an independent predictor for 12 month lethality (OR 0.986 [95%-CI:0.967–1.002]; p < 0.12). Conclusions Temperature control in surgically treated patients with space-occupying MCA infarction using a pre-specified protocol excluding temperature management systems resulted in mild hyperthermia between 36.8 °C and 37.2 °C and a low overall temperature load. Future prospective studies on larger cohorts comparing different strategies for normothermia treatment including temperature management devices are needed.